Robotically Assisted Para-aortic Lymphadenectomy. Issue 3 (March 2015) - Hudry, Delphine; Ahmad, Sarfraz; Zanagnolo, Vanna; Narducci, Fabrice; Fastrez, Maxime; Ponce, Jordi; Tucher, Elisabeth; Lécuru, Fabrice; Conri, Vanessa; Leguevaque, Pierre; Goffin, Frédéric; Holloway, Robert W.; et al.
<x xml:space="preserve">Abstract</x> Objectives The aim of this study was to evaluate perioperative outcomes of robotic-assisted laparoscopic para-aortic lymphadenectomy (PAL) in patients with gynecologic cancers during the learning phases of robotic surgery programs and to compare results of extraperitoneal versus transperitoneal approaches of PAL. Materials and Methods This study is a retrospective multicentric study of patients who underwent robotically assisted laparoscopic PAL (N = 487). Eleven European centers and 1 US center participated in the study. Abstracted data included age, body mass index, indication, type of surgical approach (transperitoneal or extraperitoneal), associated surgical procedures, operative time, estimated blood loss, lymph node count, hospital length of stay (LOS), and complications. Para-aortic lymphadenectomy was performed by an extraperitoneal approach in 58 cases (12%) and transperitoneal in 429 cases (88%). Results The mean (SD) para-aortic lymph node count was 12.6 (8.1), operative time was 217 (85) minutes, estimated blood loss was 105 (110) mL, and LOS was 2.8 (3.2) days. Four (0.8%) conversions to open and 2 (0.4%) conversions to laparoscopy were described. There were 32 lymphocysts (6.6%), 3 deep venous thromboses (0.6%), and 10 transfusions (2.1%). For transperitoneal approach, the average number of lymph nodes removed was higher in isolated PAL group than the hysterectomy combined group (report node counts 95% confidence interval, −7.29 to −3.52, P = 1.5 × 10−6). For isolated PAL, the LOS was shorter in the extraperitoneal group than in the transperitoneal group (report data 95% CI, −1.35 to −0.35, P = 0.001). Conclusions Robotic-assisted PAL seems safe and feasible. More lymph nodes were removed during an isolated transperitoneal PAL dissection compared with a combined procedure with hysterectomy. Extraperitoneal approach seems attractive relative to transperitoneal dissection, but the superiority of one or the other way is not demonstrated by our study.